Kontinuitas Budaya Mengemis Pada Transformasi Kampung Barak ke Kampung Baru - Nyimas Zahratul Azizah; Marshanda Sephira Harpy; Sunkina Niswatin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The phenomenon of begging, which emphasizes the hope of other people's compassion by selling the image of 'poverty', has become a sustainable social ecosystem that is unbroken from generation to generation because it has become a separate 'lifestyle' which is then interpreted by the perpetrators as part of a "profession". The stigma then explores into a hereditary habit that is cultivated in a social environment that makes the phenomenon of begging the main livelihood and becomes part of the 'lifestyle'. Begging culture as mentioned above occurs in one of the social environments in Bondowoso Regency, East Java, which for generations has continued the ecosystem of begging culture and is commonly known as "Kampung Barak" which has now been transformed empirically and the area is now named "Kampung Baru", but unfortunately the continuity of begging culture is still maintained. The social ecosystem attracts the author's attention to explore the phenomenon of an uninterrupted begging culture (continuity) that occurs in the transformation of "Kampung Barak" to "Kampung Baru". This research was conducted using an ethnographic approach that studies the culture and daily life of a group or community with the aim of understanding the norms, values, and practices applied in the context of cultural things. Thus, it is hoped that this research can explore and understand in depth what causes the continuity of begging culture in the transformation of "Kampung Barak" into "Kampung Baru" and be able to provide solutions to break the begging culture ecosystem in the area.